A Developmental Perspective to Attention-Deficit Hyperactivity Disorder (ADHD) in Children - Afolabi, Olusegun Emmanuel (East European Journal of Psycholinguistics, 2016)
The debate about diagnoses and treatment of attention deficit hyperactive disorder (ADHD) in children continue to range on between the developmental and biological perspectives. While there is increasing evidence that support the biological susceptibility of the disorder, a number of researches also emphasized the significant effect of environment on the syndrome. This study used developmental perspectives to evaluate and bring together various bio-psychosocial factors that impact on children diagnosed with ADHD. The study explored and integrated the existing and advancing study on ADHD to a more refined pattern that embraced developmental perspectives. The study also discussed how the linkage in childhood ADHD fits within the developmental psychopathology perspective. The study revealed that ADHD as a developmental disorder is influenced by prenatal, biological and psychosocial environmental risk factors, and suggested that better understanding of genomic susceptibilities, family environment and parental characteristics would transform the pathway for development of ADHD in children.
Keywords: attention deficit hyperactive disorder; developmental perspectives; childhood disorder; genetic factors; environmental factors